Modeling the number of car theft using Poisson regression - Zulkifli, Malina; Ling, Agnes Beh Yen; Mat Kasim, Maznah; Ismail, Noriszura (2016)
Regression analysis is the most popular statistical methods used to express the relationship between the variables of response with the covariates.The aim of this paper is to evaluate the factors that influence the number of car theft using Poisson regression model. This paper will focus on the number of car thefts that occurred in districts in Peninsular Malaysia. There are two groups of factor that have been considered, namely district descriptive factors and socio and demographic factors.The result of the study showed that Bumiputera composition, Chinese composition, Other ethnic composition, foreign migration, number of residence with the age between 25 to 64, number of employed person and number of unemployed person are the most influence factors that affect the car theft cases. These information are very useful for the law enforcement department, insurance company and car owners in order to reduce and limiting the car theft cases in Peninsular Malaysia.